Dirichlet Eigenvalue Problem of Degenerate Elliptic Operators with Non-Smooth Coefficients (Communications in Mathematical Research, 2022)
The aim of this review is to introduce some recent results in eigenvalues problems for a class of degenerate elliptic operators with non-smoothcoefficients, we present the explicit estimates of the lower bound and upperbound for its Dirichlet eigenvalues.